Mastering digital photography and imaging - Burian, Peter K. (Sybex, 2004)
This book is suited for people with little understanding of photography who are looking to get started with a digital camera. It guides techniques for getting scans of exceptional quality, whether you’re scanning prints, slides, or negatives... and tips on optimizing your images for use in e-mail, online albums, and web pages.